Deprescribing of Medicines in Care Homes-A Five-Year Evaluation of Primary Care Pharmacist Practices - Ana Alves; Shaun Green; Delyth H James (MDPI AG, 2019)
(1) Background: This project evaluates the outcomes of a novel pharmacy-led model of deprescribing unnecessary medications for care home patients. A feasibility study was conducted in 2015 to explore exposure to inappropriate polypharmacy in patients residing in care homes over a one-year timescale. The aim of this study was to present the results of this ongoing service evaluation over a five-year period. (2) Methods: Data collection and risk assessment tools developed during the feasibility study were used to measure the prevalence, nature, and impact of deprescribing interventions by primary care pharmacists over a five-year period. A random sample of approximately 5% of safety interventions were screened twice yearly by the pharmacist leads as part of standard practice. (3) Results: Over a period of five years there were 23,955 interventions (mean 2.3 per patient) reported from the 10,405 patient reviews undertaken. Deprescribing accounted for 53% of total estimated financial drug savings, equating to £431,493; and 16.1% of all interventions were related to safety. (4) Conclusions: Medication reviews in care homes, undertaken by primary care pharmacists who are linked to GP practices, generate a wide range of interventions commonly involving deprescribing, which contributes significantly to the continuous optimisation of the prescribing and monitoring of medicines.